Carotid Artery Calcification Detected on Panoramic Radiography Is Significantly Related to Cerebrovascular Accident, Coronary Artery Disease, and Poor Oral Health: A Retrospective Cross-Sectional Study - Anmol Brar; Katherine DeColibus; D. Shane Rasner; Angela R. Haynes; Frank Pancratz; Oreoluwa Oladiran; Semiu O. Gbadamosi; Adepitan A. Owosho (MDPI AG, 2024)
Panoramic radiography imaging modality is widely used by dentists for diagnosing dental and jaw conditions. It can also detect carotid artery calcification (CAC), indicative of calcified atherosclerotic plaques in the carotid arteries. This cross-sectional retrospective study at the University of Tennessee Health Science Center investigated the link between CAC identified on panoramic radiograph (PR) and cerebrovascular accident (CVA), coronary artery disease (CAD), and poor oral health. Data from 314 CAC patients collected from 2014 to 2023 included age at diagnosis, gender, and clinical histories of hypertension, hyperlipidemia, diabetes mellitus, CVA, CAD, and the decay, missing, and filled permanent teeth (DMFT) index. These patients were age- and gender-matched with non-CAC patients for analysis. The findings revealed high prevalences of hypertension (86.2%), hyperlipidemia (57.6%), diabetes mellitus (30.7%), CVA (15.5%), and CAD (28.7%) amongst CAC patients and the average DMFT index was 26.6. A comparative analysis of 276 matched controls demonstrated significant differences in hypertension (85.9% vs. 57.6%), hyperlipidemia (58.3% vs. 33.7%), diabetes (32.6% vs. 22.1%), CVA history (14.9% vs. 5.1%), CAD (26.1% vs. 9.8%), and DMFT scores (26.3 vs. 23.7), all indicating strong associations between CAC and these health conditions. The adjusted analysis showed that hypertension (aOR: 3.20 [95% CI: 2.06-5.07]), hyperlipidemia (aOR: 1.70 [95% CI: 1.14-2.50]), CVA (aOR: 2.20 [95% CI: 1.13-4.30]), and CAD (aOR: 2.10 [95% CI: 1.28-3.60]) were significantly associated with CAC. Notably, only 41.7% of the patients received a medical consultation after CAC detection on PR. It is crucial for dentists to refer patients for further evaluation.